Cobalt Carbodiimide as Negative Electrode for Li‐Ion Batteries: Electrochemical Mechanism and Performance. Issue 19 (8th October 2019) - Jiju Arayamparambil, Jeethu; Mann, Markus; Fraisse, Bernard; Iadecola, Antonella; Dronskowski, Richard; Stievano, Lorenzo; Sougrati, Moulay Tahar
Abstract: Cobalt carbodiimide, CoNCN, shows outstanding performance as negative electrode material for Li‐ion batteries, maintaining a reversible capacity of 530 mAh g −1 over 140 cycles at a current density of 540 mA g −1 . The electrochemical lithiation/delithiation mechanism of cobalt carbodiimide was investigated using complementary in situ X‐ray diffraction and X‐ray absorption spectroscopy. Upon lithiation, CoNCN undergoes a reversible conversion reaction, forming Li2 NCN and fcc Co metal nanoparticles, which are transformed back into CoNCN upon delithiation. However, the CoNCN obtained electrochemically after delithiation do not recover the local structure of the pristine phase, and might contain the NCN 2− ligand in the cyanamide isomer form (N−C≡N 2− ). It would be the first time that a transition metal cyanamide isomer is obtained at ambient conditions. Abstract : Intriguing conversion mechanism : The reaction mechanism of cobalt carbodiimide with lithium was established combining in situ XRD and XAS analyses. A conversion reaction involving ultra‐small cobalt particles and dilithium cyanamide is evidenced. This mechanism is behind the outstanding electrochemical performance of CoNCN with high and stable capacity (530 mAh g −1 at 2 C)